Pseudoproduction, Pseudocost and Profit Functions in Monopoly from the Dual Perspective - Vrankić Ilko; Krpan Mira (Business Systems Research, 2016)
Background: Duality in the microeconomic theory enables us to represent consumers’ preferences and production technology with various dual functions satisfying certain regularity conditions.